An integrated‐process model of service quality, institutional brand and behavioural intentions. Issue 5 (2014) - Parves Sultan; Ho Yin Wong
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to develop and test an integrated‐process model/an index model by incorporating the antecedents and consequences of service quality in a higher education context. Design/methodology/approach – This research employed both qualitative and quantitative research methods. The data from three focus groups, conducted at an Australian University, generated key themes and their interrelationships. The theoretical model was then tested using the structural equation modelling (SEM) technique on a sample of 528 University students. Findings – The findings show that information (or marketing communications) and past experience are the antecedents of perceived service quality (PSQ). PSQ is a second order construct and has three dimensions: academic, administrative and facilities. The consequences of PSQ include trust, satisfaction, university‐brand (UniBrand) performance and behavioural intentions. Overall, the results suggest a good validity of the model, and the nine path coefficients are found statistically significant. Originality/value – The model explains how service quality is formed, and how PSQ affects UniBrand and positive behavioural intentions overtime. This paper develops and validates three new constructs including information, past experience and UniBrand performance. In addition, it improves and validates other constructs including service quality, satisfaction, trust and behavioural intention. The paper also advances service quality literature and validates five hypothesised relationships between constructs that are relatively new in the service quality literature. Finally, this study validates a comprehensive three‐tiered "integrated‐process" model/an index model that includes antecedents, dimensions and consequences of service quality taking a University as a case. Universities aiming for a sustainable presence in a competitive global market and intending to enhance brand performance and attract and retain students are encouraged to consider this model and its implications. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors wish to thank the Editor(s) and the reviewers for their valuable comments. The authors are also grateful to Associate Professor Robert O'Sullivan for proof reading this paper. </ack>